Legal aspects of Shariah governance practices in Sri Lankan Islamic Financial Institutions: a literature review - Hayathu Mohamed Ahamed Hilmy; Rusni Hassan; Hayathu Mohamed Abdul Moujooth; M. S. A. Riyad Rooly; S. Issath Nimzith (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2022)
Purpose — This study intends to examine the legal aspects and the actual practices of Shariah governance in Sri Lanka’s IFIs. Further, it examines the law and regulations on Shariah governance as well as identifies the macro and micro level application of Shariah governance in Sri Lanka.Research method — The literature observation and document analysis were applied to explore the relevant domestic and international regulation on Shariah governance in the country. As a qualitative study, the data were gathered through the primary sources such as the information derived from the interview with experts, legislations, international Shariah standards, annual reports and other institutional documents from the IFIs; and supported by the secondary data available in the literatures such as articles in journals, books, newspaper reports, the IFIs websites, and other sources.Result — The findings of this study indicate that there is no legislation in Sri Lanka that legally enforces on Shariah governance framework at macro level. But, each IFIs has setup Shariah governance institutionally at micro level.Recommendation — The recommendations are put forward to fill the gap found and to improve the legal status of Shariah governance in Sri Lankan Islamic financial industries.